2014
DOI: 10.1371/journal.pone.0113918
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Proteomics Approach for the Search of Pharmacological Targets of the Antimalarial Clinical Candidate Albitiazolium in Plasmodium falciparum Using Photocrosslinking and Click Chemistry

Abstract: Plasmodium falciparum is responsible for severe malaria which is one of the most prevalent and deadly infectious diseases in the world. The antimalarial therapeutic arsenal is hampered by the onset of resistance to all known pharmacological classes of compounds, so new drugs with novel mechanisms of action are critically needed. Albitiazolium is a clinical antimalarial candidate from a series of choline analogs designed to inhibit plasmodial phospholipid metabolism. Here we developed an original chemical prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…Using alkyne/azide-coupling partners through "click chemistry," we identified several cytochrome P450 enzymes that metabolized deltamethrin in rat liver microsomes (10). More recently, a chemical proteomic approach was developed to identify parasite proteins targeted by an albitiazolium antimalarial drug candidate in situ using a photoactivation cross-linking approach (11). However, this generic approach can introduce significant promiscuity in the proteins tagged based on the intracompartmental distribution of drug independent of actual mechanisms.…”
mentioning
confidence: 99%
“…Using alkyne/azide-coupling partners through "click chemistry," we identified several cytochrome P450 enzymes that metabolized deltamethrin in rat liver microsomes (10). More recently, a chemical proteomic approach was developed to identify parasite proteins targeted by an albitiazolium antimalarial drug candidate in situ using a photoactivation cross-linking approach (11). However, this generic approach can introduce significant promiscuity in the proteins tagged based on the intracompartmental distribution of drug independent of actual mechanisms.…”
mentioning
confidence: 99%
“…A typical chemical strategy is synthesis of compound analogs to incorporate a “click” handle to facilitate drug target identification and validation in P. falciparum 95 . For example, a bifunctional compound based on the clinical candidate albitiazolium was synthesized that was photoactivatable and taggable 96 . MS identified a discrete list of potential drug targets in P. falciparum , while bioinformatic and interactome analyses were used to predict protein functions 96 .…”
Section: Proteomic Approaches Of Target Assignmentmentioning
confidence: 99%
“…For example, a bifunctional compound based on the clinical candidate albitiazolium was synthesized that was photoactivatable and taggable 96 . MS identified a discrete list of potential drug targets in P. falciparum , while bioinformatic and interactome analyses were used to predict protein functions 96 . As albitiazolium inhibits phospholipid metabolism, most of the target proteins are involved in lipid metabolic activities 96 .…”
Section: Proteomic Approaches Of Target Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC 50 values against 3D7 for CQ and 64 were 42.7 and 349.3 nM, respectively [35]. This approach has recently been successfully employed by the Vial group in Montpellier to search for pharmacological targets of the antimalarial clinical candidate albitiazolium by integrating photo-crosslinking and click chemistry [36]. In this study, the authors identified proteins involved in phospholipid metabolism, lipid binding and transport, as well as in vesicular transport functions through whole cell imagery, in-gel detection with fluorescent reporters and affinity purification.…”
Section: Patents Reviewmentioning
confidence: 99%